Circulating RNA differences between patients with stable and progressive idiopathic pulmonary fibrosis. Issue 3 (10th September 2020) - Clynick, Britt; Jo, Helen E.; Corte, Tamera J.; Glaspole, Ian N.; Grainge, Christopher; Hopkins, Peter M.A.; Reynolds, Paul N.; Chapman, Sally; Walters, E. Haydn; Zappala, Christopher; Keir, Gregory J.; Cooper, Wendy A.; et al.
Idiopathic pulmonary fibrosis (IPF) is a chronic disease characterised by progressive decline in pulmonary function. The rate of decline can vary, with some patients remaining stable over longer periods of time and others rapidly progressing [1]. The variable progression of this disease makes it difficult to elucidate pathogenic pathways involved in the initiation and progression of IPF. Advances in high-throughput gene-expression analyses have led to improvements in our understanding of disease biology and prognostic gene signatures. We hypothesise that IPF has a unique circulatory transcriptional profile compared to healthy controls, with additional differences between stable and progressive disease likely related to disease pathogenesis. Gene expression differences were found in the circulation of IPF patients versus healthy controls, of which five were expressed in higher concentrations in progressive versus stable IPF, potentially providing insight into disease pathogenesis https://bit.ly/3bakHCL